In vitro phototoxicity of ultradeformable liposomes containing chloroaluminum phthalocyanine against New World Leishmania species - Hernández, Indira Paola (2012)
The use of photodynamic therapy (PDT) against cutaneous leishmaniasis (CL) based on chloroaluminum phthalocyanine (ClAlPc) is a promissory alternative therapy. The main purpose of this article was to assess the internalization and in vitro phototoxic activities of ClAlPc encapsulated in ultradeformable liposomes (UDL-ClAlPc) in Leishmania parasites and mammalian cells. Cell internalization was determined by fluorescence microscopy, cell and parasite damage by standard MTT or direct microscopic analysis and a phototoxic index (PI) was calculated as the compound activity (IC50) at 0 J/cm 2/IC50 at 17 J/cm2. Liposomal and free ClAlPc were internalized by infected and non-infected THP-1 cells and co-localized in the mitochondria. Treatment of UDL-ClAlPc was almost 10 times more photoactive than free ClAlPc on THP-1 cells and promastigotes and intracellular amastigotes of Leishmania chagasi and Leishmania panamensis. Liposomal compounds were active on non-irradiated and irradiated cells however PI higher than 50 were calculated. PI for amphotericin B referential drug were lower than 1.2. Empty liposomes tested at the same lipid concentration of active ClPcAl-liposomes were non-toxic. Upon photodynamic treatment a nonselective-parasite activity against intracellular amastigotes were observed and loss of membrane integrity resulting in a release of parasites was detected. Further studies oriented to evaluate both the state of infection after PDT and the effectiveness of UDL as delivery vehicles of ClAlPc in CL experimental models are required.